On Second-Best National Saving and Game-Equilibrium Growth - Phelps, E. S.; Pollak, R. A. (Review of Economic Studies, 1968)
E. S. Phelps, R. A. Pollak; On Second-Best National Saving and Game-Equilibrium Growth1, The Review of Economic Studies, Volume 35, Issue 2, 1 April 1968,